Design of Horizontal Axis Wind Turbine Simulator Using Smart Monitoring System - Ahmad Fauzan Adziimaa; Ilham Kurniawan; Anida Oktavia Rachmadianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Wind turbine shows the direct utilization of mechanical energy and occurs as follows: the wind that moves hitting the wing of the ferris wheel causes the ferris wheel to spin. The rotation of the ferris wheel causes the formation of mechanical energy, while the conversion of wind energy into electrical energy is as follows: the wind through the ferris wheel plants causes the ferris wheel to spin. The spin of the ferris wheel causes the generator to spin. Inside the wind energy generator is converted into electrical energy. In the Final Task that did the design of this prototype, do a comparison between the horizontal axis wind turbine with variations in the number of blades, with blade variations totaling 3 and 5. So, there will be 2 wind turbines with different numbers of blades in one prototype. Comparisons are made to find out the performance carried out by the two wind turbines that aim as a learning medium in the Measurement Instrumentation Laboratory. This final task is divided into five stages: including, tool design, tool characterization, tool validation, tool testing, and comparing tools. The process of designing tools that are divided into two methods, namely covering the formation of hardware and the formation of software. From the graph data contained in the discussion shows the performance with the propeller amounting to 5 produces a higher current and voltage output and rpm on this prototype scale than the number of propellers 3, with the value for example at the acceleration of fan 5 with a wind speed of 3.9 m / s on the propeller amounting to 5 resulting in an average current value of 3.2 mA, a voltage of 1.98 V, and rotor rotation of 234 RPM. While at the number of propellers 3 with the same wind speed produces smaller current output, voltage and rpm, which is obtained an average current of 2.3 mA, a voltage of 1.88 V, and rotor rotation of 243 RPM.